Chronic High-Fat Feeding Affects the Mesenchymal Cell Population Expanded From Adipose Tissue but Not Cardiac Atria. (30th October 2015) - Perbellini, Filippo; Gomes, Renata S.M.; Vieira, Silvia; Buchanan, Dougal; Malandraki-Miller, Sophia; Bruyneel, Arne A.N.; Sousa Fialho, Maria da Luz; Ball, Vicky; Clarke, Kieran; Faggian, Giuseppe; Carr, Carolyn A.
Abstract : This study examined the effect of a high-fat diet on mesenchymal cells from cardiac and adipose tissues. It was found that a high-fat diet did not affect cardiac progenitor cells but increased the number of fibroblasts and hematopoietic cells within the adipose-derived mesenchymal cell population. Abstract: : Mesenchymal stem cells offer a promising approach to the treatment of myocardial infarction and prevention of heart failure. However, in the clinic, cells will be isolated from patients who may be suffering from comorbidities such as obesity and diabetes, which are known to adversely affect progenitor cells. Here we determined the effect of a high-fat diet (HFD) on mesenchymal stem cells from cardiac and adipose tissues. Mice were fed a HFD for 4 months, after which cardiosphere-derived cells (CDCs) were cultured from atrial tissue and adipose-derived mesenchymal cells (ADMSCs) were isolated from epididymal fat depots. HFD raised body weight, fasted plasma glucose, lactate, and insulin. Ventricle and liver tissue of HFD-fed mice showed protein changes associated with an early type 2 diabetic phenotype. At early passages, more ADMSCs were obtained from HFD-fed mice than from chow-fed mice, whereas CDC number was not affected by HFD. Migratory and clonogenic capacity and release of vascular endothelial growth factor did not differ between cells from HFD- and chow-fed animals. CDCs from chow-fed and HFD-fed mice showed no differences in surface marker expression, whereas ADMSCs from HFD-fed mice contained more cells positive for CD105, DDR2, and CD45, suggesting a high component of endothelial, fibroblast, and hematopoietic cells. Both Noggin and transforming growth factor β-supplemented medium induced an early stage of differentiation in CDCs toward the cardiomyocyte phenotype. Thus, although chronic high-fat feeding increased the number of fibroblasts and hematopoietic cells within the ADMSC population, it left cardiac progenitor cells largely unaffected. Significance: Mesenchymal cells are a promising candidate cell source for restoring lost tissue and thereby preventing heart failure. In the clinic, cells are isolated from patients who may be suffering from comorbidities such as obesity and diabetes. This study examined the effect of a high-fat diet on mesenchymal cells from cardiac and adipose tissues. It was demonstrated that a high-fat diet did not affect cardiac progenitor cells but increased the number of fibroblasts and hematopoietic cells within the adipose-derived mesenchymal cell population.